2017
DOI: 10.1007/s11060-017-2692-5
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of neuropsychological functions, APOE and amyloid imaging in patients with gliomas

Abstract: Brain tumor patients treated with radiotherapy (RT) often develop cognitive dysfunction, and recent studies suggest that the APOE ε-4 allele may influence cognitive outcome. The ε-4 allele is known to promote beta (β) amyloid deposition in the cortex, and preliminary evidence suggests that RT may be associated with this process. However, it is unknown whether β-amyloid accumulation contributes to treatment neurotoxicity. In this pilot study, we assessed neuropsychological functions and β-amyloid retention usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In addition, mean performances for Letter Fluency appeared higher in carriers than non-carriers at baseline, but similar at 12month follow-up, which indicates more improvement in non-carriers. These tests measure different facets of executive function, and a significant difference for Digit Span Backward was also found in previous research [36]. Future investigations may therefore focus primarily on executive measures.…”
Section: Still Differences For Baseline Proportions Of Impairment Digit Spansupporting
confidence: 62%
See 4 more Smart Citations
“…In addition, mean performances for Letter Fluency appeared higher in carriers than non-carriers at baseline, but similar at 12month follow-up, which indicates more improvement in non-carriers. These tests measure different facets of executive function, and a significant difference for Digit Span Backward was also found in previous research [36]. Future investigations may therefore focus primarily on executive measures.…”
Section: Still Differences For Baseline Proportions Of Impairment Digit Spansupporting
confidence: 62%
“…We note some methodological differences between studies that might account for the different findings. The longitudinal study by Correa and colleagues [36] that reported a ε4-related risk for decline A longitudinal study by Ahles et al [50] investigating changes from pre-up to 18 months post-chemotherapy in breast cancer patients also found no main effect of APOE. Late cognitive effects of treatment-induced processes that continue >6 months after radiation, such as capillary loss [52] and apoptosis [53], may be captured better at later follow-ups than those in our study.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations